Cholesterol removal from adult skeletal muscle impairs excitation–contraction coupling and aging reduces caveolin-3 and alters the expression of other triadic proteins - Barrientos, Genaro; Llanos, Paola; Hidalgo, Jorge; Bolaños, Pura; Caputo, Carlo; Riquelme, Alexander; Sánchez, Gina; Quest, Andrew F. G.; Hidalgo, Cecilia (Frontiers in Physiology, 2015)
Cholesterol and caveolin are integral membrane components that modulate the function/location of many cellular proteins. Skeletal muscle fibers, which have unusually high cholesterol levels in transverse tubules, express the caveolin-3 isoform but its association with transverse tubules remains contentious. Cholesterol removal impairs excitation-contraction coupling in amphibian and mammalian fetal skeletal muscle fibers. Here, we show that treating single muscle fibers from adult mice with the cholesterol removing agent methyl-β-cyclodextrin decreased fiber cholesterol by 26%, altered the location pattern of caveolin-3 and of the voltage dependent calcium channel Cav1.1, and suppressed or reduced electrically evoked Ca2+ transients without affecting membrane integrity or causing sarcoplasmic reticulum calcium depletion. We found that transverse tubules from adult muscle and triad fractions that contain 10% attached transverse tubules, but not sarcoplasmic reticulum membranes, contained caveolin-3 and Cav1.1; both proteins partitioned into detergent-resistant membrane fractions highly enriched in cholesterol. Aging entails significant deterioration of skeletal muscle function. We found that triad fractions from aged rats had similar cholesterol and RyR1 protein levels compared to triads from young rats, but had lower caveolin-3 and glyceraldehyde 3-phosphate dehydrogenase and increased Na+/K+-ATPase protein levels. Both triad fractions had comparable NADPH oxidase (NOX) activity and protein content of NOX2 subunits (p47phox and gp91phox), implying that NOX activity does not increase during aging. These findings show that partial cholesterol removal impairs excitation-contraction coupling and alters caveolin-3 and Cav1.1 location pattern, and that aging reduces caveolin-3 protein content and modifies the expression of other triadic proteins. We discuss the possible implications of these findings for skeletal muscle function in young and aged animals.